Safety classification of herbal medicine use among hypertensive patients: a systematic review and meta-analysis - Dain Choi; Dain Choi; Hyea Bin Im; Hyea Bin Im; Soo Jeung Choi; Soo Jeung Choi; Soo Jeung Choi; Dongwoon Han; Dongwoon Han; Dongwoon Han (Frontiers Media S.A., 2024)
BackgroundThe use of herbal medicines (HMs) for the treatment of hypertension (HTN) is increasing globally, but research on the potential adverse effects and safety of HMs in HTN patients is limited. Therefore, this systematic review and meta-analysis aim to determine the global prevalence of HM usage among HTN patients and assess the safety of identified herbs based on current scientific evidence.MethodsThe PubMed/MEDLINE, EMBASE (Ovid), and Cumulated Index to Nursing and Allied Health Literature (CINAHL) databases were searched for cross-sectional studies on the use of HM among HTN patients. Our review includes studies published in English up to the year 2023. After extracting and appraising the data from the studies, a meta-analysis was conducted using the Stata version 16.0 to estimate the pooled prevalence of HM use in patients with HTN (PROSPERO: CRD42023405537). The safety classification of the identified HM was done based on the existing scientific literature.ResultsThis study analyzed 37 cross-sectional studies from 21 countries and found that 37.8% of HTN patients used HM to manage their health. The prevalence of HM use varied significantly based on publication year and geographical region. Among the 71 identified herbs, Allium sativum L., Hibiscus sabdariffa L., and Olea europaea L. were the most commonly used. However, four herbs were identified as contraindicated, 50 herbs required caution, and only 11 herbs were considered safe for use.ConclusionThe study highlights the potential risks of toxicities and adverse effects associated with HM use in the treatment of HTN. Ensuring patient safety involves using safe HMs in appropriate doses and avoiding contraindicated HMs. Future research should focus on identifying commonly used herbs, especially in resource-limited countries with poor HTN management, and additional clinical research is required to assess the toxicity and safety of commonly used HMs.